The influence of dehydration on the interfacial bonding, microstructure and mechanical properties of poly(vinyl alcohol)/graphene oxide nanocomposites. (November 2015) - Chen, Jian; Gao, Ying; Liu, Wenlin; Shi, Xiangru; Li, Linqi; Wang, Zengmei; Zhang, Yao; Guo, Xinli; Liu, Gang; Li, Wei; Beake, Ben D.
Abstract: The relationship between the interfacial bonding, microstructure and mechanical properties of the poly(vinyl alcohol)/graphene oxide nanocomposites (PVA/GO) has been investigated by controlling the water content through a dehydration process. The interfacial bonding in PVA/GO was predominantly by hydrogen bonds which were strongly affected by the dehydration process. Micro-voids in the microstructure formed after dehydration due to the shrinkage of the fibrils. A variety of hydrogen bonds including water–water, water–GO and water–PVA can be replaced with the strong PVA–GO interfacial bond resulting in a transition from ductile to brittle fracture. The tensile modulus and strength properties of the PVA and PVA/GO increased as the amount of residual water reduced, while the fracture strain was decreased. The surface mechanical properties of PVA/GO measured by nanoindentation showed broadly similar trends with water content as the bulk mechanical properties. However, there was a threshold value of approximately 3 wt.% water below which the surface mechanical properties decrease slightly. The indentation modulus was higher than the tensile modulus by a factor of at least three. The combined influence of the microstructure and the distribution of water in the nanocomposite is considered to be responsible for this.